2023
DOI: 10.1037/rep0000505
|View full text |Cite
|
Sign up to set email alerts
|

The use of mindfulness-based interventions in stroke rehabilitation: A scoping review.

Abstract: Purpose/Objective: There is emerging evidence for the use of mindfulness-based interventions (MBIs) to improve health outcomes in the context of stroke rehabilitation. This scoping review identified recently available evidence and possible research gaps regarding how MBIs affect psychological and physical rehabilitation outcomes in individuals poststroke. Research Method/Design: Electronic searches were performed using the four major databases, CINAHL, MEDLINE, PsycINFO, and Web of Science. Sixteen studies out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
(234 reference statements)
0
8
0
Order By: Relevance
“…77 years median; IQR 67-85 [44]), and well educated. Mind-body practices such as yoga and mindfulness typically attract younger, well-educated adults, predominantly female [15,45,46]. In study 2, in which we used only online recruitment methods, we extended the recruitment catchment area to include participants from across the UK; however, as people from diverse ethnic minority communities and from areas of socioeconomic deprivation were not adequately represented in our sample, in future work, in collaboration with equality and diversity specialists, and relevant NGOs we will further develop the recruitment strategy to ensure greater representativeness.…”
Section: Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…77 years median; IQR 67-85 [44]), and well educated. Mind-body practices such as yoga and mindfulness typically attract younger, well-educated adults, predominantly female [15,45,46]. In study 2, in which we used only online recruitment methods, we extended the recruitment catchment area to include participants from across the UK; however, as people from diverse ethnic minority communities and from areas of socioeconomic deprivation were not adequately represented in our sample, in future work, in collaboration with equality and diversity specialists, and relevant NGOs we will further develop the recruitment strategy to ensure greater representativeness.…”
Section: Recruitmentmentioning
confidence: 99%
“…Following stroke, systematic review evidence indicates MBSR may be bene cial across a range of outcomes including depression and anxiety [14]. A recent scoping review found mixed evidence regarding mindfulness interventions as effective psychological interventions poststroke and indicated that further research is warranted [15].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, several studies have examined the effectiveness of mindfulness-based interventions (MBIs) in improving health outcomes for people with various diseases [9], including stroke [10,11]. Mindfulnessbased approaches, such as mindfulness-based stress reduction (MBSR) [12] and mindfulness-based cognitive therapy (MBCT) [13], focus on accepting the facts of reality in adaptively coping with difficulties [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…distress, depression, anxiety, fatigue, quality of life, well-being, mindfulness, sleep quality, and styles of coping) and physical outcomes (i.e. pain, blood pressure, and heart rate), including cardiovascular disease [15], cancer [16], chronic pain [17], diabetes [18], fibromyalgia [19], multiple sclerosis [20,21], traumatic brain injury [22,23], and stroke [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation